Prototype of Smart Home and Monitoring Application Based On Internet of Things (IoT) Using Android - Andika Fajar Isnanto; Atikah Surriani; Sri Lestari; Unan Yusmaniar Oktiawati (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2020)
Smart Home is one of the popular technological advances and developed by researchers or academics because of its high potential to be implemented in various fields. Smart Home is an Internet of Things based technology, which means that by connecting to the internet everyone can connect whenever and wherever they are. With the presence of smart home, it can simplify human problems and limitations. This paper describes the design and prototype of smart Home based on Internet of Things Applications on Android. There is an android application that functions to control and monitor the smart home. By using NodeMCU, is used as a line communication device between users and smartphones. The use of databases in Firebase makes the data on the smart home always real-time active because it is connected to Google servers. We also develop an android application; thus smart home can be controlled by its owner. Keywords: Smart Home, Internet of Thing, Android, Firebase.